Discovery and Innovation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Discovery and Innovation' is a quarterly journal, published by the African Academy of Sciences and the Third Word Academy of Sciences. The Editor 'Discovery and Innovation' Academy of Science Publishers PO Box 14798 Nairobi KENYA